Development of a Low-Power, Low-Cost Electric Energy Meter Reader with Prepaid Scratch Card Billing System (International Journal of Food and Nutritional Sciences, 2023)
The proposed system aims to develop a low-power, cost-effective electric energy meter reader comprising measurement and communication modules. The measurement module employs current and potential transformers to gauge line current and voltage, facilitating wattage and energy measurement. Outputs from these transformers undergo conversion, rectification, filtering, attenuation, and analog-to-digital conversion. Energy consumption data is transmitted to both the power supplier and consumer via SMS at predefined intervals, with the system also detecting and notifying the power company of meter tampering